Study on Urban Fabric and Public Space in Macau (Architects Association of Macau, 2012)

Depiction of the freedom of the press and access to sources of information for working journalists in Macau - Rato, Frederico; Simões, José Manuel; Flores, Rui (Macau Portuguese and English Press Association, 2017)

Computer Literacy Teaching Using Peer Learning and under the Confucian Heritage Cultural Settings of Macao, China - Wong, Kelvin; Neves, Ana; Negreiros, Joao (International Association for the Development of the Information Society, 2017)
University students in Macao are required to attend computer literacy courses to raise their basic skills levels and knowledge as part of their literacy foundation. Still, teachers frequently complain about the weak IT skills of many students, suggesting that most of them may not be benefiting sufficiently from their computer literacy courses. This research proposes an enhanced framework based on constructivist principles by using peer-tutoring to increase cost effectiveness and to improve student outcomes. Essential to this proposed model is the training of former course graduates as peer-instructors to achieve high quality learning results. At Instituto de Formação Turistica (IFT), a case study was used to evaluate its effectiveness using a qualitative analysis. In Macao, most students have a Confucian Heritage Cultural (CHC) background and the current findings demonstrate that students share more easily their learning difficulties within their group as their interpersonal relationships improve. It is suggested that since CHC cooperative learning is primarily based on bonds, students involved in this "relationship-first, learning-second" type shared a larger amount of knowledge and social skills, a dual positive outcome. Moreover, English language is a major barrier for the understanding of the teacher's message to Chinese students. Meanwhile, the negative Western concept of plagiarism is replaced, under the CHC, as the "face giving" and it is directly based on the relationship intensity to "help friends". At last, peer-tutors play a key role in the student increase internal motivation regarding the joy of the learning process. [For the complete proceedings, see ED579282.]
Publication Title: International Association for Development of the Information Society ERIC Number: ED579300
Keywords: Action Research; Asian Culture; Case Studies; College Students; Computer Literacy; Confucianism; Cooperative Learning; Cost Effectiveness; Cultural Influences; English (Second Language); Foreign Countries; Grades (Scholastic); Language of Instruction; Models; Participant Observation; Peer Relationship; Peer Teaching; Program Effectiveness; Qualitative Research; Questionnaires; Semi Structured Interviews; Student Attitudes; Student Journals; Student Surveys; Teaching Methods

Syntactic and lexical typology of Macau Patuá and Malacca Creole Portuguese. - Baxter, Alan N. (University of Saint Joseph, 2018)

nventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country [Research Report] - Morais, Isabel; Baxter, Alan (University of Saint Joseph, 2018)

Inventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country - Morais, Isabel; Baxter, Alan N. (University of Saint Joseph, 2018)
A study of Portuguese cultural vestiges assimilated into the local cultures of the island of Flores, in Eastern Indonesia, and maintained today. The vestiges include, principally, street theatre (the Bobo tradition) as well as ritual traditions inherited through the Confraternities established by Dominican missionaries in the 16th century.
Funded by Fundação Macau